Thank You, UMP - Nadira Hana, Abdul Hamid (2019)
“Thank you, UMP”, was the remark from one of the recipients for “Back to School’ Programme. He is amongst 101 recipients for the programme that were celebrated in the event held on 18 December 2019, in UMP Gambang Campus.